A brief review on hydrometallurgical technologies for recycling spent lithium‐ion batteries. Issue 7 (1st April 2013) - Chagnes, Alexandre; Pospiech, Beata
Abstract Lithium‐ion battery is a mature technology that is used in various electronic devices. Nowadays, this technology is a good candidate as energy storage for electric vehicles. Therefore, much research is focused on the development of high‐density power lithium‐ion batteries. Government regulations force manufacturers to recycle the batteries for safety and health reasons but recycling could also be interesting from an economic viewpoint since cathodes in lithium‐ion batteries contain valuable metals. The electrodes in lithium‐ion batteries will evolve to provide more energy and the recycling processes will have to fit with this evolution. Leaching, bioleaching and solvent extraction are at the centre of these processes. In this paper, recent leaching and solvent extraction strategies for recovering valuable metals from spent lithium‐ion batteries are reviewed and the evolution of these processes is discussed. © 2013 Society of Chemical Industry